Stress management and sexual health of young adults: a pilot randomised controlled trial. (8th November 2013) - Dimou, P. A.; Bacopoulou, F.; Darviri, C.; Chrousos, G. P.
Summary Young people often experience excessive stress that definitely undermines their sexual life and leads them to adopt risky sexual behaviours. As such, the design and application of a stress management programme in this particular age group is, undoubtedly, a crucial matter. In this parallel randomised controlled trial, 60 psychology students of the Panteion University of Athens, aged 18–20, were randomly assigned to undergo either an 8‐week stress management programme (n = 30; diaphragmatic breathing–progressive muscle relaxation and guided imagery, twice a day) or not (n = 30). Self‐reported validated measures were used to evaluate stress, stressful life events, health locus of control, general health status, sexual behaviours, sexual desire, satisfaction from sexual life and interpersonal relationships. Between‐group analyses revealed statistically significant differences in internal health locus of control and general health evaluation. Within the intervention group analyses showed reductions in BMI, stress, the 'chance' subscale of multidimensional health locus of control (MHLC) and greater satisfaction from sexual life. No other significant change was reported. We deem that our results should encourage relevant future studies.